2020
DOI: 10.3390/app10186401
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Effects of Landfill Soil Gases on Landfill Elevated Subsurface Temperature

Abstract: Subsurface temperature is a critical indicator for the identification of the risk associated with subsurface fire hazards in landfills. Most operational landfills in the United States (US) have experienced exothermic reactions in their subsurface. The subsurface landfill area is composed of various gases generated from chemical reactions inside the landfills. Federal laws in the US mandate the monitoring of gases in landfills to prevent hazardous events such as landfill fire breakouts. There are insufficient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A badly operated active gas extraction system or a poorly-designed leachate recirculation system is likely to allow air into the waste mass (Copping et al, 2007) which promotes the fire at landfill sub-surface. Several studies (Needham et al, 2003; Sabrin et al, 2020; Stearns and Petoyan, 1984) were carried out on temperature monitoring for the Hanover landfill which was under operation during 1936–1980. It was reported that the temperature increased up to 30 m depth from landfill surface and then it decreased towards the base.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A badly operated active gas extraction system or a poorly-designed leachate recirculation system is likely to allow air into the waste mass (Copping et al, 2007) which promotes the fire at landfill sub-surface. Several studies (Needham et al, 2003; Sabrin et al, 2020; Stearns and Petoyan, 1984) were carried out on temperature monitoring for the Hanover landfill which was under operation during 1936–1980. It was reported that the temperature increased up to 30 m depth from landfill surface and then it decreased towards the base.…”
Section: Discussionmentioning
confidence: 99%
“…Gases like CO, O 2 , CH 4 and CO 2 were determined by inserting steel probes around the landfills and through the gas extraction wells (Department of Environmental Management, 2008). Sabrin et al (2020) investigated relationship between the sub-surface elevated temperature (SET) and landfill gases (i.e. CH 4 , CO 2 , CO, nitrogen (N) and oxygen).…”
Section: Landfill Fire Detection Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas generated by the decomposition of organic matter is called biogas or landfill gas (LFG). It is composed of 45-60% methane (CH 4 ), 40-60% carbon dioxide (CO 2 ), 2-5% nitrogen (N2), 0.1-1% oxygen (O 2 ), and other gas fractions in lower percentages, including ammonia (NH 3 ), carbon monoxide (CO), hydrogen (H), sulfides, and non-methane organic compounds (NMOC) such as benzene, vinyl chloride, and trichloroethylene [10].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulated heat from exothermic reactions and the volatility of the gases generated make landfills prone to surface fires and the slow-burning of MSW below [10]. High temperatures affect the proper functioning of landfills, influencing gas generation, leachate quality, slope stability, and landfill integrity, and may also affect human health and the environment due to gas emissions into the atmosphere and the release of incomplete combustion products as a result of fires [17,18].…”
Section: Introductionmentioning
confidence: 99%